Penggunaan model pembelajaran problem based learning untuk meningkatkan kemampuan literasi sains siswa kelas V sekolah dasar - Zamil Maariz, Nur Aisyah; Ghiyats Ristiana, Muhammad; Susilawati (COLLASE (Creative of Learning Students Elementary Education), 2025)
The This research is based on the low scientific literacy abilities of elementary school students in science learning. This is based on the results of interviews conducted with class V teachers before the research was conducted. The aim of this research is to determine the increase in students' scientific literacy using the Problem Based Learning learning model. This research was conducted using the Mix Method with The Sequential Explanatory Design. The instrument used is a test instrument for students' scientific literacy abilities. The subjects in this research were class V students in one of the elementary schools in West Bandung Regency, totaling 38 students. The research results show that there is an increase in students' scientific literacy skills using the Problem Based Learning model. This can be seen from the average N-Gain gain of 0.88 and being in the "High" category. Therefore, it can be concluded that the Problem Based Learning model is effective in increasing students' scientific literacy abilities.